OIL AND GAS VOCABULARY IN THE CONTEMPORARY CHINESE LANGUAGE: A TERMINOLOGICAL AND DISCURSIVE ANALYSIS (Journal of Oriental Studies, 2025)
This article examines the influence of English-language discourse on the formation and development of oil and gas terminology in the Chinese language. Under the conditions of globalization and international cooperation, China's terminological system undergoes active borrowing and adaptation of foreign lexical units, which leads both to the enrichment of professional language and to challenges in translation and terminology unification.The study analyzes the main borrowing mechanisms, including calquing, transliteration, and semantic adaptation. Special attention is given to the challenges of translating oil and gas terminology, which arise due to the absence of direct equivalents, differences in term structure models, and the influence of cultural factors. Contemporary approaches to standardization and unification of industry-specific vocabulary are considered, including the development of dictionaries, the use of international standards, and the implementation of electronic databases for the professional community.Based on the analysis conducted, possible directions for further research are proposed, including automated translation of technical terminology, the study of borrowing dynamics, and a comparative analysis of oil and gas vocabulary in China and other Asian countries. The findings of this study may be useful for specialists in the oil and gas industry, translators, and researchers engaged in linguistics and technical communication.Keywords: oil and gas terminology, the Chinese language, English-language discourse, translation, adaptation, standardization, international standards, technical communication.